Literatur Review : Analisis Faktor Pembekuan Darah dan Gambaran Radiologi pada Pasien Covid 19 - Basri, Hasri Ainun; Syahril, Erlin; Damopolii, Suciati; Damopolii; Kamaluddin, Irna Diyana Kartika (Universitas Pahlawan Tuanku Tambusai, 2024)
COVID-19 is a contagious illness caused by a newly identified coronavirus, Sars-Cov 2 (Severe Acute Respiratory Syndrome Coronavirus 2), which was identified in 2019. Thrombocytopenia, increased D-dimer, delayed prothrombin time, and disseminated intravascular coagulation were among the abnormalities of blood clotting factors seen in COVID-19 patients. Increased D-dimer concentrations, slightly reduced platelet counts, and delayed prothrombin time are typical findings in individuals with coagulopathy who are infected with COVID-19. To confirm a diagnosis of COVID-19 in individuals infected with SARS-CoV-2, radiographic tests such CT scans and thoracic photographs are required. Radiological examinations and CT-Scan and thoracic photo which is often found ground glass opacities, crazy-paving, pleural effusion, sub-pleural bands, pulmonary edema, consolidation, reticular opacities and paracardiac atelectasis, traction bronchiectasis and vacuolar signs. This study aims to analyse blood coagulation factors and radiological features in covid 19 patients. A Literature Review with a Narrative Review is the methodology used in this research. Secondary data sourced from electronic sites such as Pubmed, Clinical Key, and Springer Link provide the bulk of this study's data set. Articles were found using the following keywords: COVID-19, radiological imaging, blood clotting factors. In order to address the research issue statement, 20 research papers were chosen from the scope literature. Radiological imaging and blood clotting factors in COVID-19 patients were reported in 20 separate investigations. The review's findings suggest that radiographic exams for coagulation abnormalities and ground glass opacities are common in individuals with severe COVID-19 infection.